Didactic model of the subject History of Cuba for the comprehension- expression of medical students - Olga Lydia Paz Figueroa; José Manuel Ubals Álvarez; Lilianis Becerra Paz (Revista Habanera de Ciencias Médicas)
Introduction: In order to train the Doctor of Medicine that society demands from the Medical University, it is necessary to narrow the gap between the insufficient development of the comprehension-expression process in students entering the Medical School and the preventive and promotional paradigm stated in the professional profile. This implies improving the teaching-learning process in all disciplines in the study plan, including the subject History of Cuba. Objective: To design a didactic model of the subject History of Cuba for the development of the comprehension-expression of medical students in the gradual approach to the object of the profession. Material and Methods: Educational research with dialectical- materialistic approach and qualitative design that used empirical methods: Documentary Review and Open Observation; theoretical methods: Modeling, Systemic-Structural and Consultation to Specialists; techniques: Workshop, and the Grid; and instruments: Logbook. Methodological triangulation was carried out. Results: A didactic model of the subject History of Cuba for the development of comprehension-expression in the gradual approach to the object of the profession, is characterized as being flexible, participative, open and collaborative. Conclusions: The designed didactic model is based on dialectically related conceptions: philosophical, psychological, pedagogical and didactic; it expresses the relationships among the participants involved, the dimensions, the key components and the phases through which it must pass, centered on the student's protagonism. The new model incorporates a multiple and recombinant integration of the comprehension-expression category, directing the attention to the change of the professional´s performance in his radius of action.